Analysis on the fabrication of porous nano titanium dioxide ceramic using Spark Plasma Sintering (SPS) - Hamizah Ahmad Khairi (2016)
Bone regeneration and bone ingrowth has been a forefront issue in tissue engineering. Many studies and experiments have been made to explore the possibilities of using bio-ceramics that are porous to repair, regenerate and replace human bone tissues, while maintaining the safety of using such a material and keeping practicality in mind. It has been widely known that although high porosity levels is crucial to ensure better biological tissue integration, it compromises on the mechanical strength of the bio-ceramics fabricated. Hence, it is important that the mechanical property is not entirely diminished so as to maximize both functions of the bio-ceramic as both a bone ingrowth inducer and temporary pillar of support to the entire site before the entire process of bone regeneration or bone repair is complete. The objective of the research is to analyse the impact of two different porogen content by %wt on TiO_2-based ceramics that is fabricated using Spark Plasma Sintering (SPS) method through the observation of both mechanical and biological testing. Analysis is made on the mechanical properties of porous TiO_2 that is sintered with the SPS method; keeping other sintering parameters of pressure and hold time constant. Sintered samples undergo compressive loading testing and another batch of samples are soaked in Simulated Body Fluid (SBF) for two weeks and observations using scanning electron microscope were made. TiO_2has been discovered to have apatite-forming ability, which is critical in ensuring the integration of the biomaterials and the host bone tissue at site. Fabricating porous TiO_2using SPS method was generally successful as the sintered samples were able to undergo both mechanical testing without failure. It was highlighted that high densification of the sintered sample eliminates the effect of high porosity within the material. Another point worth noting is that although large pores are ideal for bone growth in scaffolds, the porosity level matters. It was concluded that the most ideal sintering temperature is 650℃, attaining the highest compressive strength and capable of storing energy before fracturing despite its relatively low young’s modulus.